An Experimental Study of the Flexural Performance of Hybrid Internally Reinforced Concrete Beams with Steel Bars, FRP Bars, Geogrid, and GFRP Mesh - Khudhair, Ban Abd Abbas; Al-Khafaji, Hayder Mohammed (Engineering, Technology & Applied Science Research, 2025)
This study investigates the flexural performance of Reinforced Concrete (RC) beams internally reinforced with steel bars, Glass Fiber Reinforced Polymer (GFRP) bars, geogrid, and GFRP meshes. The experimental program consists of casting and testing twelve RC beams, including one reference beam without any strengthening and 11 strengthened beams. The key variables examined involve the number and material type of reinforcement mesh layers as well as the number and diameter of GFRP bars. The results indicate that increasing the area of added GFRP bars enhances the ultimate strength by about 37.90% and 20.22% for the beam with two GFRP bars with a diameter of 10 mm and two of 8 mm, respectively, concerning the reference beam. The increase in the area of added GFRP mesh is directly proportional with the beam failure load. The geogrid mesh improved the ultimate strength of the beams slightly more than the GFRP mesh. The addition of reinforcing mesh generally led to an increase in the Ductility Factor (DF) of the beams, but it appeared that the use of geogrid mesh led to an even greater increase. Finally, the mixing of geogrid and GFRP mesh did not significantly affect the DF value.